System recovery method considering start sequence and recovery process of direct current transmission system - LOU YUANYUAN; LI XINWEI; LI LI; YANG GUOYIN; LIU CHONGRU; LUO GANG; QIAN FENG; WU GUOBING (2018)
The invention discloses a system recovery method considering the start sequence and recovery process of a direct current transmission system, which belongs to the technical field of power system operation and control. The method comprises the steps that the problems of direct current transmission system controlling and unlocking methods, a direct current start method and a direct current start condition under a black start condition are considered firstly, and direct current start priority indexes are re-established for the characteristics of the direct current transmission system; and secondly, under the condition that the stable operation of a power system is ensured, a system recovery model in which the direct current transmission system participates is established to optimize the direct current transmission system to participate in the system recovery process, and the direct current power is improved during the system recovery process. The method fully considers the impact of starting the high-voltage dir